Data-Driven Collaborative Governance to Strengthen Social Advocacy and Public–Community Partnerships for Sustainable Development - Hazhar Talaat Abubaker Blbas; Kamran Abdullayev; Masnur Putra Halilintar (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
This community engagement program aims to strengthen collaborative governance and social advocacy in Erbil through a data-driven approach that empowers both public institutions and local communities. The initiative responds to the growing need for evidence-based decision-making, particularly in urban areas where socio-economic disparities, limited data literacy, and fragmented public–community communication hinder sustainable development efforts. Using participatory mapping, digital data collection, and community workshops, the program integrates statistical tools and informatics-based solutions to support transparent governance practices. Activities include capacity-building sessions, community needs assessments, data visualization training, and stakeholder forums designed to enhance cooperative problem-solving. Findings show that community members developed increased awareness of data-based decision processes, while local institutions improved their ability to integrate citizen input into planning. Participant feedback confirms higher trust levels, better communication pathways, and enhanced motivation to co-design development initiatives. The program demonstrates that data-driven social advocacy can strengthen relational accountability and foster long-term collaborations between stakeholders. This model offers a scalable and adaptable framework for cities in the Kurdistan Region seeking to implement more inclusive and sustainable governance strategies. Overall, the program contributes to the advancement of participatory governance by embedding statistical literacy and digital tools into community-centered development processes.